Tuning the Reactivity and Bonding Properties of Metal Square-Planar Complexes by the Substitution(s) on the Trans-Coordinated Pyridine Ring - Dvořáčková, Olga; Chval, Zdeněk (ACS omega, 2020)
The kinetics of the hydration reaction on trans-[Pt(NH3)2(pyrX)Cl]+ (pyr = pyridine) complexes (X = OH-, Cl-, F-, Br-, NO2 -, NH2, SH-, CH3, C≡CH, and DMA) was studied by density functional theory calculations in the gas phase and in water solution described by the implicit polarizable continuum model method. All possible positions ortho, meta, and para of the substituent X in the pyridine ring were considered. The substitution of the pyr ligand by electron-donating X's led to the strengthening of the Pt-N1(pyrX) (Pt-NpyrX) bond and the weakening of the trans Pt-Cl or Pt-Ow bonds. The electron-withdrawing X's have exactly the opposite effect. The strengths of these bonds can be predicted from the basicity of sigma electrons on the NpyrX atom determined on the isolated pyrX ligand. As the pyrX ring was oriented perpendicularly with respect to the plane of the complex, the nature of the X···Cl electrostatic interaction was the decisive factor for the transition-state (TS) stabilization which resulted in the highest selectivity of ortho-substituted systems with respect to the reaction rate. Because of a smaller size of X's, the steric effects influenced less importantly the values of activation Gibbs energies ΔG ⧧ but caused geometry changes such as the elongation of the Pt-NpyrX bonds. Substitution in the meta position led to the highest ΔG ⧧ values for most of the X's. The changes of ΔG ⧧ because of electronic effects were the same in the gas phase and the water solvent. However, as the water solvent dampened electrostatic interactions, 2200 and 150 times differences in the reaction rate were observed between the most and the least reactive mono-substituted complexes in the gas phase and the water solvent, respectively. An additional NO2 substitution of the pyrNO2 ligand further decelerated the rate of the hydration reaction, but on the other hand, the poly-NH2 complexes were no more reactive than the fastest o-NH2 system. In the gas phase, the poly-X complexes showed the additivity of the substituent effects with respect to the Pt-ligand bond strengths and the ligand charges.